Ergonomic study on wrist rehabilitation therapy (WRist-T) device - Nurul Ain, Abdul Shukor; Idris, Mat Sahat; Mohd Azrul Hisham, Mohd Adib (Springer Singapore, 2018)
The emerging issue in complex joints such as human wrist is usually the disability to be precisely coordinated with a traditional mechanical joint. In such cases, mechanical differences between human and robotic joints could lead to musculoskeletal disorder (MSD) and overconstraint due to the device over rotation, misalignment of the rotation axis and also the design of the device. This paper focuses on ergonomic comparison studies between the previous and present WRist-T devices. The result of the ergonomic study especially on anthropometry and ergonomic evaluation shows that the present model is better than the previous one.